Determinant Analysis Considered Consumers of Waropen Regency in Using Marine Express Sea Transportation Fleet Offered by PT. Papua Mandiri Bubble Biak Branch - Pieter N De Fretes; Ramandey Ramandey; Agoeng Karyanto (Budapest International Research and Critics University, 2022)
Management of PT. Belibis Papua Mandiri Biak Branch is required to be able to understand consumer attitudes and behavior, especially the consideration factors related to consumer preferences for sea transportation services in consumers' subjective thoughts. In order to determine the relationship between these considerations and preferences, an empirical study is needed as the basis for the formulation of a new policy that is contributive to efforts to expand the company's market share in the future in Waropen Regency. The research method is qualitative. The results of the partial correlation analysis based on the Spearman Rank Correlation Coefficient approach show that the largest partial correlation coefficient is found in the relationship between browsing speed and consumer interest (r7 = 0.9847) while the smallest correlation coefficient is found in the relationship between price levels and consumer interest (r2 = 0.4963) this indicates that Roaming Speed is the main factor that stimulates consumers to use air transportation services offered by Express Bahari motorboats, while Price Level is the main factor that tends to limit consumers in using marine transportation service products.